Iodine: A Micronutrient Essential for Human Development and Survival - Ghareeb, Ozdan Akram; Ali, Qahtan Adnan; Abed, Qassim Jawell Odah (Disease and Health: Research Developments Vol. 2, 2024)
Micronutrients are essential for the body to perform its vital functions properly. A deficiency of these rare nutritional elements, or the occurrence of an overlapping of the elements and the loss of their nutritional value, can incite disturbances in the body’s nutritional metabolism, ruining the body’s health. Iodine is a crucial micronutrient necessary for the formation of thyroid hormones. Its deficiency can lead to various pathological issues due to insufficient hormone production. This article aims to examine key topics related to iodine deficiency and its effects on public health. Notably, iodine deficiency is the primary cause of endemic goiter. Additionally, consuming certain foods in excessive amounts can hinder the thyroid gland's ability to absorb iodine. Iodine deficiency profoundly affects health, influencing everything from pregnancy and child development to mental disabilities and reduced fertility in adults. According to the WHO, Universal Salt Iodization is the most effective strategy. Iodine deficiency disorders (IDD) are significant public health concerns, resulting from insufficient thyroid hormone production due to inadequate iodine intake and affect around 2 billion people worldwide. A balanced diet rich in iodine-containing foods is essential for maintaining sufficient iodine levels. Today, researchers are particularly interested in using iodine nanoparticles (INPs) for cancer diagnosis and treatment.